Correction to “Magnetic graphene oxide increases the biocompatibility and nuclear factor erythroid 2-related factor 2 antioxidant of human cumulus cells: A lab-trial study” [Int J Reprod BioMed 2024; 22: 709–716] - Fahimeh Kabiri; Tahereh Foroutan; Maryam Pashaiasl (International Journal of Reproductive BioMedicine)
The publisher has been informed of an error that occurred on pages 709 (Vol. 22; No. 9) which the p-value sign mistakenly given as > instead of <. The publisher wishes to apologize for this error. The online version of the article has been updated on 31 March 2025 and can be found at https://doi.org/10.18502/ijrm.v22i9.17475.